Content analysis of character value indicators in class v textbooks integrated thematic curriculum 2013 theme 7 subtheme 1 - Syahrial Syahrial; Asrial Asrial; Husni Sabil; Dwi Agus Kurniawan; Rahmat Perdana; Putri Fadillah (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2022)
This study aims to analyze the material’s content in thematic textbook curriculum 2013 class V theme 7 events in life in subtheme 1 event of the colonial mass nationality that contains indicators of character value in it. This research uses a qualitative approach. The type of research used is a content analysis using document studies. The subject in this study is the researcher himself. The objects used in this study are student books and curriculum teacher books 2013 revised edition 2017 grade V theme 7 events in life. The data obtained will be analyzed descriptively qualitatively with the content analysis method. The results of  analysis of this study showed that the character values encountered in the integrated thematic textbook curriculum 2013 class V theme 7 subtheme 1 national events of the colonial period are fond of reading, hard work, curiosity, creativit, love of the homeland, independent, honest, democratic, tolerance, responsibility, discipline, national spirit, and friendly/ communicative. The analysis of the contents of the integrated thematic book material curriculum 2013 is expected educators can be more competitive and have innovations in designing learning that is able to implement character values in every learning activity for students.